The changeling : a novel - LaValle, Victor., 1972- (Spiegel & Grau, 2017)
"The wildly imaginative story of one man's thrilling odyssey through an enchanted world to find his wife, who has disappeared after having seemingly committed an unforgivable act of violence, from the award-winning author of The Devil in Silver and Big Machine"--